2020
DOI: 10.1038/s42003-020-01221-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of redox modulation on chloroplast ATP synthase

Abstract: In higher plants, chloroplast ATP synthase has a unique redox switch on its γ subunit that modulates enzyme activity to limit ATP hydrolysis at night. To understand the molecular details of the redox modulation, we used single-particle cryo-EM to determine the structures of spinach chloroplast ATP synthase in both reduced and oxidized states. The disulfide linkage of the oxidized γ subunit introduces a torsional constraint to stabilize the two β hairpin structures. Once reduced, free cysteines alleviate this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 77 publications
2
34
0
Order By: Relevance
“…. Figure 3 is based on knowledge of both oxidised and reduced structures of the plant chloroplast ATP synthase [12,13].…”
Section: Regulation Of Atp Synthases In Photosynthetic Organismsmentioning
confidence: 99%
See 3 more Smart Citations
“…. Figure 3 is based on knowledge of both oxidised and reduced structures of the plant chloroplast ATP synthase [12,13].…”
Section: Regulation Of Atp Synthases In Photosynthetic Organismsmentioning
confidence: 99%
“…To understand this regulatory feature from a structural point of view, the plant chloroplast F 1 F o -ATP synthase has been recently solved by cryo -EM at high-resolution in both an oxidised (inactive) state [ 12 ] and a reduced (active) state [ 13 ]. The latter was obtained by reducing the sample with DTT and stabilising this state with the uncompetitive inhibitor, tentoxin.…”
Section: Regulation Of Atp Synthases In Photosynthetic Organismsmentioning
confidence: 99%
See 2 more Smart Citations
“…For a long time, the structure of this region remained unknown; however, since 2018, three papers have been published on this subject; two of them pertain to the structures of F o F 1 from the chloroplasts of Spinacea oleracea and the other describes the structure of the γ–ε subcomplex from a thermophilic cyanobacterium, Thermosynechococcus elongatus BP-1 ( T. elongatus ) ( 23 , 24 , 25 ). It was revealed that this region forms a unique β-hairpin structure that extends along the central coiled-coil stalk and interacts with the “DELSEED” loop of the β subunit ( Fig.…”
mentioning
confidence: 99%